(untitled) (REVISTA SAYWA, 2020)
Platelet Rich Plasma (PRP) is a platelet concentrate obtained through a blood sample, being a promising treatment option against a variety of dermatological pathologies, since it plays a role in the repair of tissues. This article aims to present its therapeutic application in two clinical applications: alopecia and acne. Although the scientific literature on this particular topic is not as extensive yet, there are some studies that have demonstrated the efficacy of this therapeutic option and in turn highlight the benefits of implementing such therapy, emphasizing its few and even non-existent side effects, demonstrating that PRP can become a therapeutic option in dermatological alterations.